Female Genital Mutilation around The World: Analysis of Medical Aspects, Law and Practice - Kandala, Ngianga-Bakwin (Springer International Publishing, 2018)
This book uses global household data to examine the prevalence, trends and geographic variation of female genital mutilation (FGM) around the world. It also addresses the underlying legal and policy aspects as well as explores the medical consequences, both immediate and long term, for those undergoing the practice. The book analyses the position of victims of this gender-based violence both from the medical and legal perspective and adopts a largely practical approach to the study of the practices, offering a fresh thinking into one of the challenges in global health and the law. In addition, it offers some insights into how health professionals can approach this category of victims and how legal practitioners can obtain a good legal result for their clients before domestic and international forums. The book addresses fundamental issues such as state liability and defences in enforcement proceedings for actions or omission of state or non-state actors, and due diligence standard in international human rights law, the main gateways available for obtaining relief for the victims of FGM. This book goes beyond the traditional debate between zero tolerance and those who wish to see the practice medicalised and tolerated and favours an advocacy programme standing firmly in favour of the right of FGM victims. This book offers a unique perspective likely to assist victims and their representatives to secure a remedy against perpetrators and the state. As such this book will be of interest to medical professionals, national and international lawyers, academics and policymakers in the field of public health.